Hereditary Non-Syndromic Sensorineural Hearing Loss : Transforming Silence to Sound - Schrijver, Iris (American Society for Investigative Pathology, 2004)
Tremendous progress has been made in our understanding of the molecular basis of hearing and hearing loss. Through recent advances, we have begun to understand the fascinating biology of the auditory system and unveiled new molecular mechanisms of hearing impairment. Changes in the diagnostic impact of genetic testing have occurred, as well as exciting developments in therapeutic options. Molecular diagnosis, which is already a reality for several hearing-associated genes, will doubtlessly continue to increase in the near future, both in terms of the number of mutations tested and the spectrum of genes. Genetic analysis for hearing loss is mostly used for diagnosis and treatment, and relatively rarely for reproductive decisions, in contrast to other inherited disorders. Inherited hearing loss, however, is characterized by impressive genetic heterogeneity. An abundance of genes carry a large number of mutations, but specific mutations in a single gene may lead to syndromic or non-syndromic hearing loss. Some mutations predominate in individual ethnic groups. For clinical and laboratory diagnosticians, it is challenging to keep abreast of the unfolding discoveries. This review aims to provide the framework pertinent to diagnosticians and a practical approach to mutation analysis in the hearing impaired.